Information seeking behaviors of individuals impacted by COVID-19 international travel restrictions: an analysis of two international cross-sectional studies - McDermid, Pippa; Craig, Adam; Sheel, Meru; Blazek, Katrina; Talty, Siobhan; Seale, Holly (Frontiers in Communication, 2023)
Access to accurate information during a crisis is essential. However, while the amount of information circulating during the COVID-19 pandemic has increased exponentially, finding trustworthy resources has been difficult for many, including those affected by international travel restrictions. In this study, we examined the information-seeking behaviors of individuals seeking to travel internationally during the COVID-19 pandemic. We also explored perceptions regarding the value of resources in supporting understanding of COVID-19 travel restriction-related information. Two online cross-sectional surveys targeting four groups were conducted. The groups targeted were: (1) citizens and permanent residents stranded abroad; (2) individuals separated from their partners; (3) individuals separated from immediate families; and (4) temporary visa holders unable to migrate or cross international borders. In total, we analyzed 2,417 completed responses, and a further 296 responses where at least 75% of questions were completed. Findings suggest that social media groups (78.4%, 1,924/2,453), specifically Facebook (86.6%, 2,115/2,422) were the most useful or most used information resource for these groups. Some significant information seeking behavior differences across age and gender were also found. Our study highlights the diversity in information needs of people impacted by COVID-19 travel restrictions and the range of preferred channels through which information is sought. Further, it highlights which challenges hold legitimacy in their target audiences' eyes and which do not. Policymakers may use these results to help formulate more nuanced, consumer-tailored—and hence likely more acceptable, trusted, and impactful—communication strategies as part of future public health emergencies.